Determinasi Manajemen Bisnis pada Perusahaan Pelayaran: (Analisis Struktur Organisasi, Kepemimpinan dan Komunikasi) - Sri Rusiyati; Mohamad Yusuf Kurniawan; Rintis Eko Widodo; Prima Widiyanto; Agus Suhendra (JURNAL RISET MANAJEMEN (JURMA), 2026)
This study aims to identify and explain the factors that influence business management, particularly through a case study of a shipping company. The research employed a descriptive qualitative approach using a literature review method. Secondary data were collected from reputable national and international journal articles that had undergone a peer review process, ensuring that the sources used were academically reliable and relevant to the research focus. The data were analyzed through content analysis and thematic analysis to identify patterns, relationships, and key themes related to business management practices. The results of the study show that organizational structure, leadership, and communication are important factors that influence the effectiveness of business management. Organizational structure contributes to the clarity of roles, responsibilities, and work coordination. Leadership affects direction, decision-making, and employee motivation, while communication supports information flow, coordination, and organizational effectiveness. The managerial implications of this study indicate that efficient business management requires a well-structured organization, effective leadership, and clear communication to support better operational performance and decision-making